Cathepsin B and S as markers for cardiovascular risk and all-cause mortality in patients with stable coronary heart disease during 10 years: a CLARICOR trial sub-study. (November 2018) - Wuopio, Jonas; Hilden, Jørgen; Bring, Carl; Kastrup, Jens; Sajadieh, Ahmad; Jensen, Gorm Boje; Kjøller, Erik; Kolmos, Hans Jørn; Larsson, Anders; Jakobsen, Janus Christian; Winkel, Per; Gluud, Christian; et al.
Abstract: Background and aims: The lysosomal cysteine proteases cathepsin B and S have been implicated in the atherosclerotic process. The present paper investigates the association between serum levels of cathepsin B and S and cardiovascular events and mortality in patients with stable coronary heart disease. Methods: The CLARICOR trial is a randomised, placebo-controlled trial investigating the effect of clarithromycin versus placebo in patients with stable coronary heart disease. The outcome was time to either a cardiovascular event or all-cause mortality. The placebo group was used as discovery sample and the clarithromycin group as replication sample: n = 1998, n = 1979; mean age (years) 65, 65; 31%, 30% women; follow-up for 10 years; number of composite outcomes n = 1204, n = 1220; respectively. We used a pre-defined multivariable Cox regression model adjusting for inflammation, established cardiovascular risk factors, kidney function, and use of cardiovascular drugs. Results: Cathepsin B was associated with an increased risk of the composite outcome in both samples after multivariable adjustment (discovery: multivariable ratio (HR) per standard deviation increase 1.12, 95% confidence interval (CI) 1.05–1.19, p  < 0.001, replication; HR 1.14, 95% CI 1.07–1.21, p  < 0.001). There was no significant association between cathepsin S and the composite outcome in either the discovery or replication sample after multivariable adjustment ( p >0.45). Secondary analyses suggest that cathepsin B was predominantly associated with mortality rather than specific cardiovascular events. Conclusions: Cathepsin B, but not serum cathepsin S, was associated with an increased risk of cardiovascular events in patients with stable coronary heart disease. The clinical implications of our findings remain to be established. Highlights: Cathepsin B and S are lysosomal proteins implicated in the atherosclerotic process. The CLARICOR trial studied the effect of clarithromycin on cardiovascular mortality. In this 10 year-follow up, Cathepsin B was associated with cardiovascular mortality. Cathepsin S was not associated with cardiovascular mortality.